Charge transport through a water-assisted hydrogen bond in single-molecule glutathione disulfide junctions. Issue 2 (12th December 2019) - Yang, Wei-Yu; Zheng, Jueting; Zhang, Xia-Guang; Chen, Li-Chuan; Si, Yu; Huang, Fei-Zhou; Hong, Wenjing
Abstract : This work demonstrates that single-molecule conductance measurements can identify reduced and oxidized glutathiones and thus have potential application in clinical diagnosis. Abstract : We report a novel strategy to identify reduced and oxidized glutathiones by employing an STM break junction technique. A mechanism involving a water-assisted hydrogen bond is proposed for the charge transport through the oxidized glutathione junction, and this is verified by both experimental and theoretical findings.